MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP PADA MATERI SPLDV DENGAN MENGGUNAKAN PENDEKATAN OPEN-ENDED - Zaenab, Zaenab; Rohaeti, Euis Eti; Afrilianto, M (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to examine and analyze the contextual approach to improve the communication skills of junior high school students. Population in this research is a student of class VIII SMP in Karawang. This classroom action research is planned to consist of 2 (two) cycles based on the syllabus of the teaching of mathematics teacher of class VIII. Each cycle is implemented in accordance with the changes to be achieved. Prior to the action, the first test is given with the intention to know the initial ability of students and related to the topic taught that is SPLDV. Based on the results and discuss the students' understanding ability has increased.